2013
DOI: 10.7314/apjcp.2013.14.3.2029
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Willingness to Accept Chemotherapy among Elderly Malaysian Patients

Abstract: Background: The geriatric population in Malaysia is predicted to increase from 4% of the total population in 1998 to 9.8% by 2020, in parallel with developments in the socioeconomy. Cancer is expected to be a major medical issue among this population. However, the decision for treatment in Malaysia is always decided by the caregivers instead of the elderly patients themselves. Objective: The aim of the study was to assess the willingness to accept chemotherapy among elderly Malaysians. Materials and Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…They believed that additional discussion about the chemotherapy would increase their confidence in making such a decision. In addition, previous study showed that the more the time spent with the patient, the more the psychological support they have while making such important decision [16]. However, in this study 90 (84.9%) patients were able to make their decision during the first meeting.…”
Section: Discussionmentioning
confidence: 58%
“…They believed that additional discussion about the chemotherapy would increase their confidence in making such a decision. In addition, previous study showed that the more the time spent with the patient, the more the psychological support they have while making such important decision [16]. However, in this study 90 (84.9%) patients were able to make their decision during the first meeting.…”
Section: Discussionmentioning
confidence: 58%
“…Dampak yang terjadi pada tahap ini adalah kondisi penyakit akan menjadi lebih buruk, karena pasien yang tidak percaya dengan diagnosa, pasien akan mengabaikan pengobatan yang sebenarnya dapat menyembuhkan penyakit tersebut (Razali, et al, 2013). Kemampuan adaptasi dari pasien kanker sangat dibutuhkan dalam menjalani tahap-tahap respon tersebut.…”
Section: Temaunclassified
“…COVID-19 patients who receive support from their family and closest relatives will greatly influence their recovery, because it can generate optimism for these patients [14]. One of the factors that influence the adaptation of someone who has just been diagnosed with a disease is optimism for recovery.…”
Section: Introductionmentioning
confidence: 99%